2014
DOI: 10.1002/ps.3798
|View full text |Cite
|
Sign up to set email alerts
|

Non‐target effects of two sunflower seed treatments on Orius insidiosus (Hemiptera: Anthocoridae)

Abstract: Thiamethoxam treatment on sunflower seeds caused lethal and sublethal effects on O. insidiosus, whereas chlorantraniliprole was not lethal to any life stage, although sublethal effects were evident. The nymphal stage was most susceptible, and insecticidal toxicity diminished with plant development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…Certain sucking predators ingest systemic insecticides by feeding on the plant, such as O. insidiosus, which is known to probe plants and remove plant juices during periods of drought or limited prey . Eggs can be directly exposed within the oviposition site, and O. insidious eggs placed in sunflowers Helianthus annuus L. grown from thiamethoxam‐treated seeds exhibited reduced adult survival and fecundity . Adult parasitoids can be directly exposed to the systemic insecticide by feeding on extrafloral nectar or guttation liquid, the latter of which is a common phenomenon during the seedling stages of corn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain sucking predators ingest systemic insecticides by feeding on the plant, such as O. insidiosus, which is known to probe plants and remove plant juices during periods of drought or limited prey . Eggs can be directly exposed within the oviposition site, and O. insidious eggs placed in sunflowers Helianthus annuus L. grown from thiamethoxam‐treated seeds exhibited reduced adult survival and fecundity . Adult parasitoids can be directly exposed to the systemic insecticide by feeding on extrafloral nectar or guttation liquid, the latter of which is a common phenomenon during the seedling stages of corn.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, their presence on the seed coating as well as the systemic activity in the plant can pose non-target risks. 7 Negative effects from direct and indirect exposure to neonicotinoids have been reported for a number of beneficial insects including: Coleoptera: Coccinellidae, Carabidae, Staphylinidae [8][9][10][11][12] ; Hemiptera: Anthocoridae, Lygaeidae, Pentatomidae, Reduviidae [13][14][15] ; Neuroptera: Chrysopidae 14,16 and hymenopteran parasitoids. 13,[17][18][19][20] Furthermore, a meta-analysis of 20 field studies 21 reported an overall approximately 16% reduction in natural enemy abundance, which was comparable to the impact caused by foliar and soil-applied pyrethroids.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, results from neonicotinoid lab and field studies present highly variable and conflicting results when assessing similar insect response metrics or even the same insect species (e.g., Orius insidiosus reproduction; Gontijo et al. , Fernandes et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous studies have recently investigated neonicotinoid effects on performance measures (e.g., reproduction, behavior) of various beneficial insect species, no quantitative synthesis of this growing body of literature currently exists. Furthermore, results from neonicotinoid lab and field studies present highly variable and conflicting results when assessing similar insect response metrics or even the same insect species (e.g., Orius insidiosus reproduction; Gontijo et al 2015, Fernandes et al 2016. Similar discrepancies exist for other species including honeybees, native bees, butterflies, and earthworms (Blacquiere et al 2012, Pisa et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Lower densities of this important food source (thrips) could, in theory, result in lower densities of O. insidiosus; however, this trend was not observed in our experiments. Direct impacts on O. insidiosus from thiamethoxam seed-treatments have been documented in previous laboratory studies, in which lethal and sublethal effects to O. insidiosus via direct exposure to thiamethoxam-treated plants were observed (Prabhaker et al 2011, Seagraves and Lundgren 2012, Gontijo et al 2015. Despite the potential for thiamethoxam treatments to have negative impacts on O. insidiosus via depletion of their food source (thrips), acute toxicity or sublethal effects, our experiments did not detect any impacts of thiamethoxam-grown snap beans on densities of O. insidiosus (Table 3).…”
Section: Field Experimentsmentioning
confidence: 75%